Manifesto form: the medium and the message - Hanna, Julian (2013)
What should a manifesto look and sound like? Most are short, visual, and slogan-filled. But how short is too short? When does a manifesto become a slogan? On the other hand, their impact diminishes rapidly as the page count increases. Manifestos are a form of advertising, and who wants to read a 200-page ad? A manifesto is meant to make its point immediately, forcefully, eschewing reasoned argument. With a bang: not a whimper. Length and visual appeal are just two aspects of manifesto form. Theatricality, narrative, collaboration, distribution, and poetic elements are some of the other features discussed in the last in a series of three essays on the manifesto written exclusively for CQN.